The Malaysian market for audit services: Ethnicity, multinational companies and auditor choice - Che Ahmad, Ayoib; Houghton, Keith A.; Mohamad Yusof, Nor Zalina (Emerald Group Publishing Limited, 2006)
Purpose – The purpose of this paper is to investigate the extent to which ethnic association (i.e.Chinese and Bumiputra ownerships) and national issues (i.e. the presence of foreign corporations)influence the audit services market in Malaysia. Specifically, the paper aims to examine the effects of ethnicity and foreign ownership on choice of auditor.Design/methodology/approach – Two logit models are used; the first is to test on ethnic auditor (Chinese/non-Chinese) choice while the second is related to the choice of quality-differentiated auditor.The data is obtained from annual reports of the population of the Bursa Malaysia listed companies for both the Main Board and the Second Board for the periods 1993-1995.Findings – The logit regressions confirm our prediction of ethnic networking and preferential treatment on the auditor selection process. Research limitations/implications – The first limitation lies on the auditor choice model where the model is developed from a demand perspective, assuming that the auditors are willing to supply services to any client even though it is very unlikely in the real world.The model also assumes that the audit engagement process for foreign-controlled companies is purely transacted in the Malaysian market.However, foreign multinational corporations might determine the selection of the auditor at the headquarter offices and the Malaysian subsidiaries might simply be directed to engage a given auditor. Another limitation relates to the results of the logit regressions as the study has documented an ethnic association between auditor and auditee rather than establishing a causal relationship. Practical implications – An important implication of these findings relates to auditor independence. The Malaysian Institute of Accountants (MIA) has made rules prescribing the code of professional conduct and ethics of public accountants known as the MIA By-Laws (on Professional Conduct and Ethics) but it seems to neglect the diversity of local culture in addressing independence. Whilst the auditor is divorced from financial and familial interests, the ethnic sentiments might impair auditor independence especially in an audit conflict situation. Originality/value – The paper provides important insights into the existence of Chinese business practices in Malaysia and auditor selection process in this country.